Anemia in Elderly Patients—The Impact of Hemoglobin Cut-Off Levels on Geriatric Domains - Francesco Salis; Giambeppe Locci; Barbara Mura; Antonella Mandas (Diagnostics, 2023)
Background: The primary aim of this study was to evaluate the impact of anemia—according to the WHO criteria—on cognitive performances, mood, functional and nutritional status, and comorbidities in a population of subjects aged 65 years or older. The secondary aim of this study was to understand if different hemoglobin cut-off levels are associated with a variation of the mentioned domains’ impairment. Methods: We designed a cross-sectional study, including subjects aged 65 or more consecutively evaluated in an outpatient setting from July 2013 to December 2019. A sum of 1698 subjects met the inclusion criteria. They were evaluated with: MMSE and CDT (cognitive assessment), GDS (mood), BADL, IADL, PPT, and POMA (autonomies), MNA (nutritional status), and CIRS (comorbidities). Results: According to the WHO criteria, non-anemic patients reported significantly better performances than the anemics in BADL (p < 0.0001), IADL (p = 0.0007), PPT (p = 0.0278), POMA (p = 0.0235), MNA, CIRS TOT, CIRS ICC, and CIRS ISC (p < 0.0001). The same tendency has been found by considering the 12 g/dL- and the 13 g/dL-cut-off level in the whole population. The multivariate analysis showed that, considering the 12 g/dL-cut-off level, age (OR: 1.03, p = 0.0072), CIRS (OR: 1.08, p < 0.0001), and gender (OR: 0.57, p = 0.0007) were significant regressors of anemia, while considering the 13 g/dL-cut-off level, age (OR: 1.04, p = 0.0001), POMA (OR: 1.03, p = 0.0172), MNA (OR = 0.95, p = 0.0036), CIRS (OR: 1.17, p < 0.0001), ICC (OR = 0.83, p = 0.018), and gender (OR = 0.48, p < 0.0001) were significant regressors of anemia, while the other CGA variables were excluded by the model (p > 0.01). Conclusions: Our study showed that anemia negatively impact on geriatric people’s general status, regardless of which hemoglobin cut-off level is considered. It also highlighted that hemoglobin concentrations < 13 g/dL, regardless of gender, have an association with the impairment of the affective-functional-nutritional state as well as an increase in comorbidities; therefore, it should be pursuable to consider the elderly person “anemic” if Hb < 13 g/dL regardless of gender.